PRAGMATIK; KONSEP DASAR MEMAHAMI KONTEKS TUTURAN - Abdurrahman, Abdurrahman (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2006)
Pragmatics is a linguistics branch which maintains the use of context in understanding and produces speech. It is used to develop principles of work relationship and politeness in communication process, therefore, the aim of communication can be gained effectively. This context itself has relationship with culture which is different from one society to another society.